SISTEM IDENTIFIKASI PERIZINAN KIR DENGAN QR-CODE BERBASIS ANDROID - Angriani, Liza; Dayat, Abd. Rachman (Jurnal Ilmiah Matrik, 2023)
The security and authenticity of a proof of KIR licensing is very important, because proof of KIR licensing is obtained after going through a series of processes and fulfilling the requirements in accordance with applicable legal rules. The Department of Transportation in the service of KIR in Jayapura City licensing issues proof of passing the KIR test in the form of a KIR book, zinc plate and stickers. In this study, the design of the KIR licensing identification system was carried out using a QR-Code based on an Android mobile application and web service. The QR-Code is used as a marker of the authenticity of the proof of KIR licensing which is added to the KIR licensing sticker. In the resulting QR-Code has been added an encrypted information using the 3DES algorithm. This study uses the waterfall model software development method which is preceded by system requirements analysis, system design, system creation, and system testing. The final result of the research that has been done proves that the use of QR-Code as an identification tool and the selection of the Android platform as a QR-Code scanner application can be used as a solution as a tool to identify the authenticity of KIR licensing.